(untitled) (Academicia Globe: Inderscience Research, 2024)
In this article, through the theoretical foundations of the development of the sense of social and professional responsibility of future teachers, the social, family and personal, social and professional sense of responsibility, the development of civic educational qualities, the issues of raising a well-rounded young generation with intellectual potential are covered by means of pedagogical influence.